2016
DOI: 10.1287/opre.2016.1482
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Process Flexibility Designs: Is the Long Chain Really Optimal?

Abstract: Sparse process flexibility and long chain has became an important concept in design flexible manufacturing systems since the seminal paper of Jordan and Graves (1995). In this paper, we study the performance of long chain in comparison to all designs with at most 2n edges over n supply and n demand nodes. We show that, surprisingly, long chain is not optimal in this class of networks even for i.i.d. demand distributions. In particular, we present a family of instances where a disconnected network with 2n edges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…It is clear that the performance of 3-chain is almost as good as the full flexibility design for all three types of service constraints. This phenomena is well-known when total capacity is fixed and the objective is to optimize demand fulfillment (Chou et al, 2011;Chen et al, 2015;Wei, 2015, 2012;Désir et al, 2016), and is also observed when the service constraints are of Type-II (Lyu et al, 2017a). Table 3 shows that even under Type-I constraints, the long chain design can achieve most of the pooling benefit of full flexibility, and the improvement from 3-chain to full flexibility is negligible.…”
Section: Optimal Capacity Level For Different Flexibility Structuresmentioning
confidence: 73%
“…It is clear that the performance of 3-chain is almost as good as the full flexibility design for all three types of service constraints. This phenomena is well-known when total capacity is fixed and the objective is to optimize demand fulfillment (Chou et al, 2011;Chen et al, 2015;Wei, 2015, 2012;Désir et al, 2016), and is also observed when the service constraints are of Type-II (Lyu et al, 2017a). Table 3 shows that even under Type-I constraints, the long chain design can achieve most of the pooling benefit of full flexibility, and the improvement from 3-chain to full flexibility is negligible.…”
Section: Optimal Capacity Level For Different Flexibility Structuresmentioning
confidence: 73%
“…They also proposed a heuristic to find such structures. Désir et al (2016) found that for some instances of demand distribution, a disconnected network performs strictly better than the long chain. They further proved that the long chain is indeed optimal among connected networks.…”
Section: Process Flexibilitymentioning
confidence: 99%
“…Wang and Zhang (2015) obtain a bound on the asymptotic performance of the long chain that only depends on the mean and variance of the demand distribution. Recently, Désir et al (2016) prove the optimality of the long chain among all connected structures with the same number of arcs. Research has also been conducted on the long chain using a graph expander.…”
Section: Literature Reviewmentioning
confidence: 99%